Discharge estimation of submarine springs in the Dead Sea based on velocity or density measurements in proximity to the water surface. Issue 2 (19th November 2019) - Munwes, Yaniv Y.; Geyer, Stefan; Katoshevski, David; Ionescu, Danny; Licha, Tobias; Lott, Christian; Laronne, Jonathan B.; Siebert, Christian
Abstract: The Dead Sea is a closed lake, the water level of which is lowering at an alarming rate of about 1 m/year. Factors difficult to determine in its water balance are evaporation and groundwater inflow, some of which emanate as submarine groundwater discharge. A vertical buoyant jet generated by the difference in densities between the groundwater and the Dead Sea brine forms at submarine spring outlets. To characterize this flow field and to determine its volumetric discharge, a system was developed to measure the velocity and density of the ascending submarine groundwater across the center of the stream along several horizontal sections and equidistant depths while divers sampled the spring. This was also undertaken on an artificial submarine spring with a known discharge to determine the quality of the measurements and the accuracy of the method. The underwater widening of the flow is linear and independent of the volumetric spring discharge. The temperature of the Dead Sea brine at lower layers primarily determines the temperature of the surface of the upwelling, produced above the jet flow, as the origin of the main mass of water in the submarine jet flow is Dead Sea brine. Based on the measurements, a model is presented to evaluate the distribution of velocity and solute density in the flow field of an emanating buoyant jet. This model allows the calculation of the volumetric submarine discharge, merely requiring either the maximum flow velocity or the minimal density at a given depth. Abstract : A vertical buoyant jet generated by the difference in densities between the groundwater and the Dead Sea brine forms at submarine spring outlets. The velocity and density of the ascending submarine groundwater across the center of the stream along several horizontal sections and equidistant depths were measured while divers sampled the spring. A model was developed to allow the calculation of the volumetric submarine discharge, merely requiring either the maximum flow velocity or the minimal density at a given depth.